2011
DOI: 10.5665/sleep.1246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sleep Deprivation on Vocal Expression of Emotion in Adolescents and Adults

Abstract: These findings support the importance of sleep for healthy emotional functioning in adults, and further suggest that adolescents are differentially vulnerable to the emotional consequences of sleep deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 37 publications
9
61
0
Order By: Relevance
“…Emotional intensity ratings have also been studied less, and may follow on from categorization decisions [57]. We suggest that future studies should focus on identifying sensitive and [67] report that sleep deprived subjects were less vocally expressive, with similar results reported by Harrison and Horne [68]. These results seem M A N U S C R I P T…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Emotional intensity ratings have also been studied less, and may follow on from categorization decisions [57]. We suggest that future studies should focus on identifying sensitive and [67] report that sleep deprived subjects were less vocally expressive, with similar results reported by Harrison and Horne [68]. These results seem M A N U S C R I P T…”
Section: Discussionsupporting
confidence: 68%
“…Following a night of sleep deprivation, subjects use fewer words, and are judged to express less positive affect and more negative affect via speech. The acoustic properties of speech are also affected by sleep deprivation, with effects on several parameters [67]. Of 30 acoustic properties studied, there was significant disruption to several properties (e.g.…”
Section: Emotional Expressivitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent experimental study showed that restricted sleep to 6.5 h for 5 days-a regimen mimicking common sleep curtailment during a school week-resulted in increased self-reports of tension, anxiety, and fatigue as well as greater parent rated oppositionality/irritability and poorer emotional regulation in adolescents aged 12-17 years (Baum et al 2014). Likewise, curtailing sleep to 6.5 h on a first night and to \2 h on a second night showed similar effects involving increased negative affect and decreased positive affect in adolescents aged 10-16 years (Dagys et al 2012;McGlinchey et al 2011;Talbot et al 2010). In a computerized analysis of emotional markers in speech, adolescents appeared to be even more vulnerable to the effects of sleep deprivation compared to adults (McGlinchey et al 2011).…”
Section: The Role Of Sleep For Depression In Adolescencesupporting
confidence: 53%
“…Likewise, curtailing sleep to 6.5 h on a first night and to \2 h on a second night showed similar effects involving increased negative affect and decreased positive affect in adolescents aged 10-16 years (Dagys et al 2012;McGlinchey et al 2011;Talbot et al 2010). In a computerized analysis of emotional markers in speech, adolescents appeared to be even more vulnerable to the effects of sleep deprivation compared to adults (McGlinchey et al 2011).…”
Section: The Role Of Sleep For Depression In Adolescencementioning
confidence: 73%